Evolving fetal phenotypes and clinical impact of progressive prenatal exome sequencing pathways: cohort study. (1st June 2022) - Mone, F.; Abu Subieh, H.; Doyle, S.; Hamilton, S.; Mcmullan, D. J.; Allen, S.; Marton, T.; Williams, D.; Kilby, M. D.
ABSTRACT: Objectives: To determine (1) the diagnostic yield and turnaround time (TAT) of two consecutive prenatal exome sequencing (ES) pathways, (2) the evolution of the fetal phenotype and (3) the clinical impact of detecting causative pathogenic variants and incidental findings. Methods: This was a retrospective cohort analysis of prospectively collected fetal cases that underwent trio ES in the presence of a structural anomaly and normal chromosomal microarray testing in the West Midlands Regional Genetics Laboratory, Birmingham, UK. The study included two phases: (1) between July 2018 and October 2020, the clinical pathway from the Prenatal Assessment of Genomes and Exomes (PAGE) study was adopted and involved prenatal trio ES based on a panel of 1542 development disorder genes and case selection by a multidisciplinary team; (2) between October 2020 and July 2021, prenatal trio ES investigation was based on the National Health Service (NHS) England R21 pathway, with definitive inclusion criteria and a panel of 1205 prenatally relevant genes. Deep phenotyping was performed throughout pregnancy and postnatally. Results: A total of 54 cases were included. The diagnostic yield before vs after R21 pathway implementation was 28.0% (7/25) and 55.2% (16/29), respectively ( P = 0.04). The respective values for mean TAT were 54.0 days (range, 14–213 days) and 14.2 days (range, 3–29 days). In cases in which a causative pathogenic variant was identified and in which the pregnancy reached the third trimester, additional anomalies were detected between the second and third trimesters in 73.3% (11/15) of cases, predominantly secondary to progressive hydropic features (3/11 (27.3%)), arthrogryposis (3/11 (27.3%)) or brain anomaly (2/11 (18.2%)). In three cases, a variant of uncertain significance was reclassified to likely pathogenic based on postnatal information. Detection of a causative pathogenic variant had a significant clinical impact in 78.3% (18/23) of cases, most frequently affecting decision‐making regarding the course of the pregnancy and neonatal management (7/18 (38.9%)). Conclusions: Prenatal ES using the NHS England R21 pathway showed great promise when applied to this cohort, allowing a genetic diagnosis to be made in over half of preselected cases with a fetal structural anomaly on ultrasound. Monitoring and real‐time updating of fetal phenotype and reclassification of variants based on postnatal findings is vital to increase the clinical impact that is already evident from this emerging genomic technology. © 2021 International Society of Ultrasound in Obstetrics and Gynecology. Abstract : Linked article: There is a comment on this article by Li and Li. Click here to view the Correspondence.